MGE-Like Neural Progenitor Cell Survival and Expression of Parvalbumin and Proenkephalin in a Jaundiced Rat Model of Kernicterus. (May 2022) - Yang, Fu-Chen; Vivian, Jay L.; Traxler, Catherine; Shapiro, Steven M.; Stanford, John A.
Kernicterus is a permanent condition caused by brain damage from bilirubin toxicity. Dystonia is one of the most debilitating symptoms of kernicterus and results from damage to the globus pallidus (GP). One potential therapeutic strategy to treat dystonia in kernicterus is to replace lost GP neurons and restore basal ganglia circuits through stem cell transplantation. Toward this end, we differentiated human embryonic stem cells (hESCs) into medial ganglion eminence (MGE; the embryological origin of most of the GP neurons)-like neural precursor cells (NPCs). We determined neurochemical phenotype in cell culture and after transplanting into the GP of jaundiced Gunn rats. We also determined grafted cell survival as well as migration, distribution, and morphology after transplantation. As in the GP, most cultured MGE-like NPCs expressed γ-aminobutyric acid (GABA), with some co-expressing markers for parvalbumin (PV) and others expressing markers for pro-enkephalin (PENK). MGE-like NPCs survived in brains at least 7 weeks after transplantation, with most aggregating near the injection site. Grafted cells expressed GABA and PV or PENK as in the normal GP. Although survival was low and the maturity of grafted cells varied, many cells produced neurite outgrowth. While promising, our results suggest the need to further optimize the differentiation protocol for MGE-like NPC for potential use in treating dystonia in kernicterus.